2020 Stimulus Coronavirus Aid, Relief and Economic Security Act: Comparative Analysis of President Roosevelt’s New Deal Programs and President Obama’s American Recovery and Reinvestment Act of 2009 - Gbolahan Solomon Osho; Michael Adams; Quonna Coleman; Matthew Uwakonye (Journal of Social and Development Sciences, 2020)
America is facing an economic disaster and is in need of federal relief to remain leading nation. Is America currently facing another Great Depression? In the 1930s the United States suffered from an economy downturn; the stock market crashed, spending declined, there was a drop in production, jobs were lost, bills went unpaid, and the market for produce reduced. President Franklin D. Roosevelt implemented the New Deal Programs to recover the economic damage of the United States. President Barack Obama inherited a stressed economy from former President George W. Bush with a national debt of $10.627 trillion. As President Roosevelt once did, President Obama is now working toward a plan to recover the damaged United States economy? The uncontainable depression later referred to as the Great Depression attacked the economy of the United States. In 2007 the United States began to take an economy downtown again. President Franklin D. Roosevelt implemented the New Deal Programs to recover the economic damage of the United States. President Barack Obama inherited a stressed economy from former President George W. Bush with a national debt of $10.627 trillion.